Results of the treatment of the patients with malignant fibro histiocytoma of low limbs soft tissues - Litvinenko, O. O.; Korovin, S. I.; Kutsenko, L. B. (Journal of Education, Health and Sport, 2019)
The basis of the research was the analysis of the results of treatment of 130 patients with malignant fibrous histiocytoma of limbs soft tissues. The patients were treated at the National Cancer Institute from 1985 to 2016. The analysis made showed that the overall survival rate of the patients under examination depends on the location of the primary tumor. Indicators of recurrence-free survival differ significantly depending on the localization of the tumor. In relapsing patients overall survival is different and depends on the method of treatment. In the course of the first six years, the indicators of overall survival are better in the patients underwent only surgical treatment. The overall survival rate for all patients with MFH depends on the treatment method.